Μετάφραση και σχολιασμός αποσπάσματος του άρθρου "Interpreters and Interpreting in conflict zones and scenarios: A historical perspective", Ruiz Rosendo, L. & Persaud, C. (2016). Interpreting in conflict zones throughout history. Linguistica Antverpiensia, New Series: Themes in Translation Studies, 15, 1-11. - (:unkn) unknown (My University, 2024)
This dissertation is an attempt to translate a specialized text about an historical approach regarding the interpretation in conflict zones and different periods of history published in Linguistica Antverpiensia, New Series: Themes in Translation Studies. The aim was to transfer it adequately, using all the tools and techniques at the translator's disposal. The translator's main focus during the translation process was to create a functional equivalent in the Target Language. The dissertation also includes the commentary of any difficulties that occurred during the translation process.
Keywords: διερμηνεία, συρράξεις, ιστορική αναδρομή, αρχαιότητα, μεταφραστικές δυσκολίες; interpretation, conflict zones, historical approach, translation difficulties